Plasma-assisted CO2 methanation: effects on the low-temperature activity of an Ni–Ce catalyst and reaction performance. Issue 10 (9th October 2019) - Ge, Yuanzheng; He, Tao; Han, Dezhi; Li, Guihua; Zhao, Ruidong; Wu, Jinhu
Abstract : Ni–Ce three-dimensional material with macropore diameter of 146.6 ± 8.4 nm was synthesized and used as a methanation catalyst. Firstly, H2 reduction of the catalyst was conducted in the thermal fixed bed and plasma reactor, respectively, then X-ray diffraction (XRD) and CO2 temperature programmed desorption experiments on the two reduced samples were carried out to reveal the plasma effect on the catalyst's physico-chemical properties. It was found that plasma reduction created more abundant basic sites for CO2 adsorption, in particular the medium basic sites were even doubled compared with the thermal-reduced catalysts. The plasma-reduced catalyst exhibited excellent low-temperature activity, ca 50–60°C lower than the thermal catalyst (the maximum CO2 conversion point). Based on the optimum reduced catalyst, plasma effect in the reactor level was further investigated under high gas hour space velocity of approximately 50 000 h −1 . The plasma reactor showed higher CO2 conversion capacity and efficiency than the thermal reactor.